ECONOMY, EXCHANGE, AND POWER: NEW EVIDENCE FROM THE LATE CLASSIC MAYA PORT CITY OF CANCUEN. Issue 1 (7th August 2014) - Demarest, Arthur A.; Andrieu, Chloé; Torres, Paola; Forné, Mélanie; Barrientos, Tomás; Wolf, Marc
Abstract: The site of Cancuen held a strategic position as "head of navigation" of the Pasión River and the physical nexus of land and river routes between the southern highlands, the Maya lowlands, and the transversal route to Tabasco and Veracruz. For that reason, the well-defined ports of Cancuen were critical to both Classic Maya highland/lowland commerce and interactions with the far west. All aspects of Cancuen were related to its role as a port city. By the late eighth century, evidence suggests that in the site epicenter peninsula ports and other aspects of the economy were elite controlled and supervised, based on associated architectural complexes, artifacts, imports, and placement. Recent evidence indicates that, in addition to previously discussed long-distance exchange in exotics such as jade and pyrite, Cancuen also was involved in very large-scale obsidian transport and production, as well as probable exchange of other piedmont commodities such as cacao, cotton, salt, achiote ( Bixa orellana ), and vanilla. Distribution of architectural, epigraphic, and iconographic evidence and an administrative/ritual palace all indicate growing roles for nobles in these economic activities, particularly the ports. It would appear that, as elsewhere, nobles were taking a more direct mercantile role and that many aspects of the multepal system of power, characteristic of Postclassic period societies, were already in place at Cancuen by the late eighth century. The failure of Cancuen's early transition to a Terminal Classic political economy may be related to its dependence on highland resources and overextended trade networks.